2019
DOI: 10.1590/1806-9282.65.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the sodium-glucose co-transporter 2 in the elderly: clinical and mechanistic insights into safety and efficacy

Abstract: SUMMARY The prevalence of type 2 diabetes mellitus (T2DM) in the elderly grew sharply over the last decade. Reduced insulin sensitivity and secretory capacity, weight gain, sarcopenia, and elevated adiposity are all common metabolic and body changes in the aging population that favor an increased risk of hypoglycemia, frailty syndrome, falls, and cognitive dysfunction. First line antidiabetic therapy is frequently not safe in older individuals because of its high risk of hypoglycemia and prevalent co-morbid di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 149 publications
(23 reference statements)
0
11
0
4
Order By: Relevance
“…This view is supported by recent clinical studies, demonstrating the use of metformin along with SGLT2 inhibition, in elderly patients 41,42 . Further, several clinical trials have demonstrated the beneficial effects of SGLT2 inhibitors on reducing cardiac morbidity risk of heart failure in the aged population 10‐12,43 …”
Section: Discussionmentioning
confidence: 83%
“…This view is supported by recent clinical studies, demonstrating the use of metformin along with SGLT2 inhibition, in elderly patients 41,42 . Further, several clinical trials have demonstrated the beneficial effects of SGLT2 inhibitors on reducing cardiac morbidity risk of heart failure in the aged population 10‐12,43 …”
Section: Discussionmentioning
confidence: 83%
“…SGLT2i therapy in older individuals was effective at lowering glucose and maintained its positive effect on body weight and systolic blood pressure, as shown in a meta-analysis of post hoc studies in which the median age of the subgroups analysed was >60 years 102 . However, specific RCTs that evaluated both the efficacy and safety of SGLT2is in the elderly population, especially in patients >75 years, are still lacking and only very limited data have been published in observational studies 103 .…”
Section: Elderly Populationsmentioning
confidence: 81%
“…Nearly 50% of patients with T2D are 65 years old or older [8]. In older patients, treatment with SGLT-2i is effective at lowering glucose, body weight and systolic blood pressure, as shown in a meta-analysis of post-hoc studies in which the median age of patients was > 60 years [56]. On the other hand, specific trials that evaluated both the efficacy and safety of SGLT-2i in older patients with T2D, especially in those > 75 years, are still lacking and only very limited data are available from observational studies [57].…”
Section: The Effect Of Agementioning
confidence: 99%